Orthotropic Elastic Characterization of FDM PLA via Multi-axial Mechanical Testing - MEHIR, Youcef (Biopolymer Applications Journal, 2026)
This study investigates the orthotropic elastic behavior of Polylactic Acid (PLA) manufactured using Fused Deposition Modeling (FDM). According to ISO 527-2 and ASTM standards, standardized tensile and shear specimens were printed along the X, Y, and Z axes. A Box–Behnken Design of Experiments (DoE) was employed to investigate the influence of three key process parameters on the mechanical response: layer thickness, raster width, and printing speed. Directional Young’s moduli (Ex, Ey, Ez) and shear moduli (Gxy, Gyz, Gzx) were obtained through mechanical testing. The results revealed a pronounced anisotropy induced by the layer-by-layer deposition process. We used the experimental data to make the full elastic stiffness matrix for the PLA, which is an orthotropic material. Statistical analysis (ANOVA) confirmed that process parameters had the biggest effect on changes in stiffness. The results give us a lot of information that we can use to model printed PLA parts in finite element simulations and help us come up with better ways to design 3D printed parts that work well mechanically.<audio class="audio-for-speech"></audio> Translator <audio class="audio-for-speech"></audio> Translator